Biomedical application of gelatin-PVA-silk fibre composite reinforced with copper and manganese substituted hydroxyapatite - Sabareeswari Kalidas; Shanmugam Sumathi (Journal of Materials Research and Technology)
In the field of tissue engineering and orthopaedics, bone regeneration is a new and promising area. Infection, inflammation, and discomfort are frequent side effects of conventional therapy for bone restoration. This study focuses on developing a novel scaffold combining polymers and ceramic materials. Polymers such as gelatin, silk fibre (natural polymers) and PVA (synthetic polymer) with ceramic (Copper-manganese- HAP) were fabricated by electrospinning technique and ceramic was synthesised by hydrothermal method. Polymer-ceramic (CuxMnxCa5-2x(PO4)3 OH) (x = 0.1 and 0.25) composite was fabricated with different wt % (20, 40, 60) of ceramic. Characterization techniques including FTIR, XRD, SEM, and EDAX were employed. The scaffold exhibited high porosity (99.84%) with the highest ceramic content. Antimicrobial evaluations against S. aureus, E. coli, and C. albicans shown (71 ± 1.56), (73 ± 1.36), (70 ± 1.60) mm and the hemolytic (%) around 0.88 for higher wt % of ceramic incorporated composite. The mineralization test in a simulated body fluid was used to assess the scaffolds' ability to generate apatite that resembles bone and it was confirmed by SEM analysis. The cell-viability study showed that MG-63 cells had successfully attached and grown on the scaffold surface. From the ALP activity it was found that osteoblast mineralization on the scaffolds increased as increasing the time interval. The fabricated scaffold, owing to its high porosity, mechanical properties and significant biological compatibility holds promise for Bone tissue engineering applications.